A review of treatment of relapsing-remitting type of multiple sclerosis (RRMS) - Arkadiusz Bydliński; Aleksandra Brożyna; Natalia Małek; Sara Emerla; Anita Kwiatkowska; Konrad Karłowicz; Maria Hermanowska; Julia Lubomirska; Patrycja Figurowska; Łukasz Ciulkiewicz; Patryk Pluta (Journal of Education, Health and Sport, 2024)
Introduction